INTENSITAS PENCAHAYAAN DAN TINGKAT KELELAHAN BELAJAR SISWI KELAS XI IPA SMA NEGERI 1 AIRMADIDI KABUPATEN MINAHASA UTARA - Sri Handayani Abdullah; Bongakaraeng Bongakaraeng; Anselmus Kabuhung (Jurnal Kesehatan Lingkungan, 2018)
Lighting is one of the important factors in the design of a space. A good school should be designed so as to improve the effectiveness of the teaching and learning process. Indonesia National Standard in 2000 classroom lighting is 250-300 lux. Measurement of Learning Fatigue was performed in 79 students of Class XI IPA using Reaction Timer tool and measurement of lighting intensity in 6 Classroom XI IPA by using Lux meter tool. The purpose of this study to determine whether there is a correlation of the intensity of lighting to the exhaustion of students studying Class XI IPA in SMA Negeri 1 Airmadidi. This research is analytic by using Cross Sectional approach that is researcher looking for correlation between independent variable (risk factor) with dependent variable (effect) by doing momentary measurement. The Intensity of Eligible Lighting is in class XI IPA VI with result 251 Lux and Student who is not tired there are 28 student and less tired as much as 51 student. To test the significance of the results obtained p value = 0,000 <value of α (0.05), thus Ha accepted and Ho rejected means there is a relationship between lighting intensity with Fatigue Student Learning Class XI IPA in SMA Negeri 1 Airmadidi Regency North Minahasa Year 2018. For further researchers measurement of lighting in the classroom is more appropriate to use local lighting that is measured directly on the table of each student's learning.